(untitled) (Journal of Hama University, 2019)
Introduction: Pallor is considered a useful clinical sign in the evaluation of patients suspected of anemia. However, the ability of identifying this sign might change in cases of Iron, Bilirubin and Melanin pigmentation. Aim: this study aims to evaluate the effect of Iron overload on the validity of using pallor in multiple anatomical sites within the oral mucosa as a clinical sign in diagnosing moderate and severe anemia among Major Beta-Thalassemia patients as a model of Iron pigmentation. Materials and Methods: the sample consists of 69 patients (44 males,25 females) aged 5 to 33 years old (Average 15.4 years) who are reported to the Department of Thalassemia, General Medical Clinics, Damascus, Syria. Visual examination of oral mucosal pallor sign takes place in four anatomic sites (hard palate, soft palate, dorsum of the tongue, buccal mucosa) by two examiners. A venous blood sample is taken and Hemoglobin level is tested. The patients records are referenced to acquire the results of the latest Ferritin serum level. Results: statistical analysis shows that the hard palate has the highest sensitivity and the lowest specificity diagnosing severe anemia, while the dorsum of the tongue has the highest specificity and the lowest sensitivity diagnosing severe anemia. This study could not find any statistically significant correlation between clinical pallor and hemoglobin value controlling for Ferritin serum level. Conclusion: Within the limits of this study, Ferritin serum level does appear to have any effect on the validity of oral mucosal pallor in diagnosing anemia among major Beta-Thalassemia Patients.